Systemic complement activation and complement gene analysis in enterohaemorrhagic Escherichia coli-associated paediatric haemolytic uraemic syndrome - Ahlenstiel-Grunow, Thurid; Hachmeister, Svenja; Bange, Franz Christoph; Wehling, Cyrill; Kirschfink, Michael; Bergmann, Carsten; Pape, Lars (Nephrology, dialysis, transplantation, 2016)
AbstractBackground. In contrast to atypical haemolytic uraemic syndrome (aHUS), only single case reports and limited data have been published on systemic activ
Gesehen am 12.08.2020